Design and test of an inside-filling pneumatic precision centralized seed-metering device for rapeseed - Yitao, Liao; Lei, Wang; Qingxi, Liao (International Journal of Agricultural and Biological Engineering, 2017)
The pneumatic precision seed-metering devices used in combination with negative air pressure to suck seed and positive air flow to drop seed could overcome the problem of rapeseed precision planting. However, these devices can only plant a single row at a time or need high airflow pressure, which complicates the seed-metering system and the seeder structure, deteriorate the working reliability and have high power consumption. To overcome above shortcomings, a novel prototype of pneumatic precision centralized seed-metering device with seed inside-filling, sowing six rows at a time, was developed. The main structure and working principle of the prototype were described and the technical parameters were given. Experiments were conducted to investigate the influences of positive pressure, negative pressure, and rotating speed on the seeding performance. The stability of each row and the consistency between all rows associated with the seeding precision were analyzed to evaluate the performance of the prototype. The results indicate that the prototype can meet the requirements of precision seeding and the seeds keep intact without any obvious damage. The performance of the prototype was no significant difference when the positive pressure was fluctuated from 200 Pa to 1200 Pa. The best seeding precision parameters in one row of the prototype was 92.48% of the qualified seeding index (Iqs) and 2.55% of the missing-seeding index (Imiss), when the rotating speed was 16 r/min, the positive pressure was 200 Pa and the negative pressure was –1600 Pa. When the rotating speed was 16 r/min, the positive pressure was 200 Pa, and the negative pressure was –1400 Pa or –1600 Pa, the Iqs of six rows were above 86.5%, the stability coefficient of variation (CV) of each row were below 4.6%, and the consistency CV were below 0.9%. Further field experiment showed that the rapeseed sowed by the prototype had acceptable seeding precision. The CV of the numbers of rapeseed seedlings in the field of the total and each row were 6.17% and 6.32% respectively. The research confirmed that the inside-filling pneumatic precision centralized seed-metering device satisfied the agronomic requirements of rapeseed planting and can be a reference for the development of precision seed metering devices.Keywords: centralized seed-metering device, seed inside-filling, pneumatic, precision sowing, rapeseedDOI: 10.3965/j.ijabe.20171002.2061Citation: Liao Y T, Wang L, Liao Q X. Design and test of an inside-filling pneumatic precision centralized seed-metering device for rapeseed. Int J Agric & Biol Eng, 2017; 10(2): 56–62.